Integrating Hadith Into Education: Bridging The Gap Between Traditional Islamic Scholarship and Modern Learning - Abdul Kodir (Prodi Ilmu Hadis Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2023)
This study aims to investigate how the integration of Hadith can address the gap between traditional Islamic scholarship and modern learning. Specifically, this study aims to examine the impact of integrating Hadith into education on enhancing education's spiritual, moral, and ethical dimensions and improving the understanding and appreciation of Islamic principles among modern learners. Additionally, the study aims to explore the potential of integrating Hadith into education to develop critical thinking skills and promote a deeper understanding of Islamic tradition, strengthening the connection between Muslims and their faith. This qualitative study uses the library research method to gather information and literature related to the research topic, such as books, journals, articles, and other documents. The study's results indicate that integrating Hadith into education has promising results in enhancing education's spiritual, moral, and ethical dimensions. By integrating Hadith into the curriculum, learners are exposed to the rich Islamic tradition and principles, which helps them understand and appreciate the values and teachings of their faith. Moreover, integrating Hadith into education can develop critical thinking skills, which are essential for learners to navigate the complexities of modern societies while maintaining a solid connection to their faith. However, potential challenges associated with integrating Hadith into education include selecting relevant Hadiths, interpreting them correctly, and ensuring that they align with modern values and principles. Therefore, educators and curriculum developers must approach the integration of Hadith into education with a critical and reflective mindset, considering the diverse perspectives and needs of the Muslim community.